2004
DOI: 10.1073/pnas.0404616101
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-regulated therapeutic gene as a preemptive treatment strategy against ischemia/reperfusion tissue injury

Abstract: Ischemia and reperfusion represent major mechanisms of tissue injury and organ failure. The timing of administration and the duration of action limit current treatment approaches using pharmacological agents. In this study, we have successfully developed a preemptive strategy for tissue protection using an adenoassociated vector system containing erythropoietin hypoxia response elements for ischemia-regulated expression of the therapeutic gene human heme-oxygenase-1 (hHO-1). We demonstrate that a single admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 32 publications
4
73
0
1
Order By: Relevance
“…This induction is of the same magnitude as the B8-fold hypoxic induction in the luciferase activity of the AAV construct driven by four tandem repeats of the erythropoietin HRE element subsequently shown in vivo to provide significant protection against I/R injury when driving the HO-1 transgene. 10 Likewise, HRE-regulated AAV-vector having nine copies of erythropoietin HRE elements yielded similar magnitude of induction of LacZ marker gene in vitro (10-to 30-fold depending on the cell type) in hypoxic conditions. 38 This vector was also shown to effectively increase the expression of vascular endothelial growth factor-A (VEGF-A) transgene in hypoxic mouse myocardium, despite significant induction of the endogenous mouse VEGF-A.…”
Section: Oxidative Stress-inducible Vectorsmentioning
confidence: 88%
See 3 more Smart Citations
“…This induction is of the same magnitude as the B8-fold hypoxic induction in the luciferase activity of the AAV construct driven by four tandem repeats of the erythropoietin HRE element subsequently shown in vivo to provide significant protection against I/R injury when driving the HO-1 transgene. 10 Likewise, HRE-regulated AAV-vector having nine copies of erythropoietin HRE elements yielded similar magnitude of induction of LacZ marker gene in vitro (10-to 30-fold depending on the cell type) in hypoxic conditions. 38 This vector was also shown to effectively increase the expression of vascular endothelial growth factor-A (VEGF-A) transgene in hypoxic mouse myocardium, despite significant induction of the endogenous mouse VEGF-A.…”
Section: Oxidative Stress-inducible Vectorsmentioning
confidence: 88%
“…3,26 Regulatable vectors offer a solution to this problem, especially if they can be regulated by endogenous stimuli relevant to the pathology. Hypoxiaactivated adeno-associated virus (AAV) vector-expressing HO-1 has been developed and successfully used for treatment of cardiac I/R injury, 10 and HO-1 gene transfer also offers protection against chronic recurrent I/R injury and prevents post-infarction heart failure. 10,27,28 AREregulated gene transcription has been shown to be a central mechanism providing protection against oxidative stress in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heme oxygenase-1 (HO-1) is an inducible protein whose expression is increased several fold in response to a variety of cellular stresses and stimuli including ischemia [3] hypoxia [4], oxidative stress [5] and inflammatory cytokines [6], suggesting an important role for this enzyme in tissue protection. Several studies have shown that HO-1 over-expression protects against ischemia/reperfusion injury in a variety of tissues including the myocardium [7][8][9][10][11]. Conversely, reduced HO-1 levels increase susceptibility to injury in a variety of stress conditions.…”
Section: Introductionmentioning
confidence: 99%